Social Media as a Tool to Facilitate Human Capital Relations to Open Innovation and Business Performance - Yulianti, Prima; Fahmy, Rahmi; Lukito, Hendra; Games, Donard (Jurnal Manajemen Teknologi, 2024)
Abstract. Companies increasingly leverage social media tools to access knowledge from external actors, particularly customers and other users, to facilitate innovation processes and corporate performance. Little empirical research has investigated the impact of external knowledge sourced through social media. This research aims to analyze the influence of human capital on open innovation and business performance through social media. This research was conducted on MSMEs in Padang City, West Sumatra, Indonesia. The sample was 200 MSMEs in Padang City. The sampling technique is purposive sampling. The quantitative method is then processed and analyzed using Structural Equation Modeling (SEM) data analysis techniques with smartPLS. This research examines how external knowledge flows of human capital sourced from social media influence open innovation and business performance. The findings in this research are that there is a positive and significant influence between human capital on business performance, human capital on open innovation, human capital on social media, and social media on open innovation. On the other hand, social media does not have a positive or significant influence on business performance. This research also shows the role of social media as a mediator of the positive and significant relationship between human capital and open innovation. Meanwhile, social media fails to mediate the relationship between human capital and company performance. Overall, these findings underscore the importance of human capital in enhancing open innovation through social media, thereby impacting firm performance.   Keywords: Human capital, social media, open innovation, business performance   Abstrak. Perusahaan semakin memanfaatkan alat media sosial untuk mengakses pengetahuan dari pelaku eksternal, khususnya pelanggan dan pengguna lainnya, untuk memfasilitasi proses inovasi dan kinerja perusahaan. Sedikit penelitian empiris yang menyelidiki dampak pengetahuan eksternal yang bersumber melalui media sosial. Penelitian ini bertujuan untuk menganalisis pengaruh modal manusia terhadap inovasi terbuka dan kinerja bisnis melalui media sosial. Penelitian ini dilakukan pada pelaku UMKM di Kota Padang, Sumatera Barat, Indonesia. Sampelnya adalah 200 pelaku UMKM di Kota Padang. Teknik penentuan sampel adalah purposive sampling. Metode yang digunakan adalah kuantitatif, kemudian diolah dan dianalisis menggunakan teknik analisis data Structural Equation Modeling (SEM) dengan smartPLS. Penelitian ini mengkaji bagaimana aliran pengetahuan eksternal dari modal manusia yang bersumber dari media sosial mempengaruhi inovasi terbuka dan kinerja bisnis. Temuan dalam penelitian ini adalah adanya pengaruh positif dan signifikan antara human capital terhadap kinerja bisnis, human capital terhadap open Innovation, human capital pada media sosial, dan media sosial terhadap open Innovation. Sebaliknya media sosial tidak mempunyai pengaruh positif atau signifikan terhadap kinerja bisnis. Penelitian ini juga menunjukkan peran media sosial sebagai mediator hubungan positif dan signifikan antara modal manusia dan inovasi terbuka. Sementara itu, media sosial gagal memediasi hubungan antara modal manusia dan kinerja perusahaan. Secara keseluruhan, temuan ini menggarisbawahi pentingnya modal manusia dalam meningkatkan inovasi terbuka melalui media sosial, sehingga berdampak pada kinerja perusahaan. Kata kunci: Modal manusia, media sosial, inovasi terbuka, kinerja bisnis